Corporate Effect of Vacuum Mixing and Freezing-thawing Treatment on Microstructure and Quality of Quick-frozen Youtiao Dough - Xingli LIU; Jing ZHANG; WU Hao; Xiaojuan YANG; Hongwei WANG; Yanyan ZHANG; Hua ZHANG (Shipin gongye ke-ji, 2022)
In order to investigate the corporate effect of vacuum mixing and freezing-thawing treatment on microstructure and quality of quick-frozen Youtiao dough and fritters, frozen Youtiao dough was prepared under the vacuum mixing (0~0.08 MPa) and freezing-thawing treatment (0~3 times). Combined analytical methods covering multiple instruments (e.g., low field nuclear magnetic resonance, scanning electron microscopy, and fourier infrared spectrum analyzer) were used to investigate the water distribution, microstructure, and secondary structure of treated frozen Youtiao dough. Meanwhile, the oil content, water content, specific volume and textural quality of Youtiao were analyzed. Results showed that freezing-thawing treatment destroyed the structure of the dough, declined the strong bonding water content of dough and α-helical content in gluten (14.80%~13.61%), resulting in the loose and disordered protein structure. However, with the increase of vacuum degree, the strong bonding water content in quick-frozen Youtiao dough gradually increased, and the ordered degree of protein network structure in dough also improved. Furthermore, freezing-thawing treatment could also decrease the volume (1.82 cm3/g~1.47 cm3/g), increase the oil content (15.08%~16.88%) and reduce the textural quality of Youtiao, while vacuum mixing could effectively decrease the oil content (15.08%~12.64%), improve volume (1.82 cm3/g~2.38 cm3/g), reduce hardness and improve other qualities of Youtiao. These results indicated that vacuum mixing could reduce the quality deterioration caused by freezing-thawing treatment by regulating the water distribution and protein structure in quick-frozen Youtiao dough. Therefore, this study can provide theoretical basis and guidance for large-scale production of quick-frozen Youtiao.